Coping Strategies and Parenting Styles in Mothers of Children with and without Attention Deficit Hyperactivity Disorder - González, Rocío; Bakker, Liliana; Rubiales, Josefina (Pensando Psicología, 2014)
The aim of this study was to compare coping strategies and the parenting styles of mothers of children who have and have not been diagnosed with Attention Deficit Hyperactivity Disorder (adhd). The sample consisted of two groups: one of mothers of a child diagnosed with adhd (n = 14) and a control group (n = 35). The methodological approach was to apply two scales that evaluate parental educational styles and the Coping Strategies Questionnaire (csq), designed to evaluate seven basic coping styles. The results show differences in the perception of parenting styles of mothers of children with adhd compared to the control group, taking the form of more criticism, less expression of affection and more rigid educational behavior. While there were no significant differences between groups in terms of the coping strategies used, a tendency could be seen among mothers of children with adhd to rely more on rational and emotional coping strategies. Identifying the most effective parenting style and coping strategies has direct implications for the treatment of this disorder, as these could have an important impact on how a child’s illness develops.